2017
DOI: 10.1097/md.0000000000007115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elastic resistance exercise on body composition and physical capacity in older women with sarcopenic obesity

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
197
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(213 citation statements)
references
References 52 publications
8
197
0
8
Order By: Relevance
“…Patients in our study also showed a significant increase in soft lean mass and skeletal muscle mass after the 12-week resistance exercise. This is consistent with the results of previous studies, where elastic band exercise training was effective in increasing the muscle mass in elderly women with aging-induced sarcopenic obesity [26,27]. This suggests that resistance exercise using elastic bands can be effective for improving body composition by inducing muscle mass increase in elderly women with obesity.…”
Section: Discussionsupporting
confidence: 92%
“…Patients in our study also showed a significant increase in soft lean mass and skeletal muscle mass after the 12-week resistance exercise. This is consistent with the results of previous studies, where elastic band exercise training was effective in increasing the muscle mass in elderly women with aging-induced sarcopenic obesity [26,27]. This suggests that resistance exercise using elastic bands can be effective for improving body composition by inducing muscle mass increase in elderly women with obesity.…”
Section: Discussionsupporting
confidence: 92%
“…Increasingly, promising studies are published underscoring this implication. 55 Effects of such programs may be enhanced by a protein-rich diet. 52 Treatment of obesity itself, even by bariatric surgery in sarcopenic patients, 53 leads to a decrease in depression.…”
Section: Discussionmentioning
confidence: 99%
“…54 Resistance training has shown benefit on body composition, muscle quality, and physical function in women with sarcopenic obesity. 55 Effects of such programs may be enhanced by a protein-rich diet. 56 Although optimal exercise programs improve depressive symptoms 57 in older people, our results suggest that the largest effects are probably found in patients with sarcopenic obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training has been well‐recognized as a safe, effective and powerful behavioural intervention for prevention and rehabilitation of chronic diseases such as coronary arterial disease, hypertension, type 2 diabetes, obesity and depression . Despite the complexity of the signs and symptoms presented in IPF, supervised exercise training is a feasible and effective treatment for clinical improvement .…”
Section: Discussionmentioning
confidence: 99%